2014
DOI: 10.4330/wjc.v6.i11.1209
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose management in the patient undergoing cardiac surgery: A review

Abstract: Both diabetes mellitus and hyperglycemia per se are associated with negative outcomes after cardiac surgery. In this article, we review these associations, the possible mechanisms that lead to adverse outcomes, and the epidemiology of diabetes focusing on those patients requiring cardiac surgery. We also examine outpatient and perioperative management of diabetes with the same focus. Finally, we discuss our own efforts to improve glycemic management of patients undergoing cardiac surgery at our institution, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
0
29
0
2
Order By: Relevance
“…Hyperglycemia is associated with increased incidence of sternal wound infections, stroke, and renal complications. [1] As the prevalence of diabetes increases in the population, the prevalence of hyperglycemia-related cardiac surgical complications is growing and deserves consideration for prevention and optimization of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia is associated with increased incidence of sternal wound infections, stroke, and renal complications. [1] As the prevalence of diabetes increases in the population, the prevalence of hyperglycemia-related cardiac surgical complications is growing and deserves consideration for prevention and optimization of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Variable glucose levels before, during and after cardiac surgery lead to increased post-operative complications and patient mortality. [1] Current methods for intensive monitoring and treating hyperglycemia in the Intensive Care Unit (ICU) usually involve hourly glucose monitoring and continuous intravenous insulin infusions. With the advent of more accurate subcutaneous glucose monitoring systems, the role of improved glucose control with newer systems deserves consideration for widespread adoption.…”
mentioning
confidence: 99%
“…This is in line with Lazar et al (44) who showed that preoperative hemoglobin A1c (HbA1c) levels were not predictive of early adverse outcomes following CABG if glycemic control was achieved. Indeed some authors suggest that preoperative HbA1c measurement should be taken in all patients, since it should reflect the adequacy of glycemic control when its level is less than 7% (45). This has been confirmed by Halkos et al (46) who found a significant association between HbA1c >7% and DSWI.…”
Section: Discussionmentioning
confidence: 88%
“…Even if the Proxima were completely accurate and precise in measurement of the parameters it does analyse, the device suffers from an inability to assess blood glucose and lactate concentrations. Given that diabetes mellitus is a substantial risk factor for coronary artery disease, and that the importance of appropriate glycaemic control intra‐operatively has been highlighted , this is a considerable drawback. Similarly, serum lactate is an important marker of metabolic‐perfusion mismatch, which correlates with outcome in cardiac surgical patients and correlates with severity of metabolic acidosis during deep hypothermic circulatory arrest .…”
Section: Discussionmentioning
confidence: 99%